Strategy of Developing Green Talao Park Marine Tourism Object in Nagari Ulakan Padang Regency, Pariaman, West Sumatra - Putrima, Andini Aulia; Bathara, Lamun; Yanti, Willy (Jurnal Perikanan dan Kelautan, 2025)
Indonesia is a country with enormous tourism potential, boasting more than 17,000 islands and a tropical climate that supports natural beauty on land and sea. However, based on data from the World Tourism Organization, the number of foreign tourists visiting Indonesia is still low compared to other countries such as Malaysia, Thailand, and Europe. This shows that Indonesia's tourism management has not been optimized. This study aims to identify and formulate a strategy for developing potential marine tourism sites in Green Talao Park, Nagari Ulakan, Padang Pariaman Regency. This study uses a qualitative approach with survey and interview methods. They use purposive sampling and accidental methods. The study was conducted by direct observation in the field. The results of this study indicate that the strategy for developing marine tourism in Green Talao is to utilize natural attractions to draw visitors and increase their numbers. Additionally, there is a need to improve the quality of human resources for the management and development of the area. Carrying capacity calculations can provide a maximum limit on the number of visitors that can be accommodated in the area. There is a need for socialization through counseling to provide an understanding of environmental pollution and the impacts of managing and utilizing potential at the Green Talao Park location